Application of Health Belief Model on Factors Influencing Long-Term Contraceptive Use - Ayu Dhiah Pitaloka; Pawito Pawito; Hanung Prasetya (Journal of Health Promotion and Behavior, 2019)
Background: Family planning is one of the strategies to reduce maternal mortality. Data in 2017 shows that in Indonesia, out of 37,338,265 couples of reproductive age there were 18.63% who did not do family planning. Women of reproductive age (WRA) who have not done family planning can affect reproductive health. This study aimed to analyze factors influencing long-term contraceptive method (LTCM) using health belief model theory.Subjects and Method: This was a cross sectional study conducted in Sleman, Central Java, from March to April 2019. A sample of 220 women of reproductive age was selected by quota sampling. The dependent variable was LTCM use. The independent variables were perceived severity, perceived susceptibility, perceived benefit, cues to action, self-efficacy, education, and culture. The data was collected by questionnaire and analyzed by a multiple logistic regression.Results: Perceived severity (OR= 8.02; 95% CI= 2.62 to 24.51; p<0.001), perceived susceptibility (OR= 12.16; 95% CI= 3.65 to 40.42; p<0.001), perceived benefit (OR= 6.05; 95% CI= 2.10 to 17.40; p= 0.001), cues to action (OR= 6.98; 95% CI= 2.30 to 21.18; p= 0.001), self-efficacy (OR= 3.60; 95% CI= 1.23 to 10.52; p= 0.019), education (OR= 2.50; 95% CI= 1.40 to 10.41; p= 0.029), culture (OR= 6.65; 95% CI= 2.14 to 20.62; p= 0.001) increased long-term contraceptive use.Conclusions: Perceived severity, perceived susceptibility, perceived benefit, cues to action, self-efficacy, education, culture increase long-term contraceptive use.Keywords: family planning, long-term contraceptive, health belief modelCorrespondence: Ayu Dhiah Pitaloka. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: ayudhiahp@gmail.com. Mobile: +62812266896291Journal of Health Promotion and Behavior (2019), 4(1): 55-63https://doi.org/10.26911/thejhpb.2019.04.01.06